CONSELHO DE CLASSE E SÉRIE PARTICIPATIVO: DIFÍCIL APRENDIZAGEM PARA UMA PRÁTICA DEMOCRÁTICA - Camacho, Martha Janete Vita (2010)
This dissertation results from a qualitative research, referred the educational policies aiming democratic practices within public schools. The focus of this study concerns to the Class Council, once it has been consolidated as an important issue, a key success factor of the democratization of school management and the teaching-learning process, improving the quality and giving the opportunity to parents and students to participate in the school processes. That research had three axis: (1) data and analysis of school documentation; (2) observation in two public schools of Sao Paulo and (3) interviews with parents, students, teachers and educational administrators. Each moment of this research could bring out a reflection concerned to the Class Council practices, from which could be proposed some considerations. The main objectives were to demonstrate how the participation process has been occurred even by discernments and errors during the school construction in a democratically process, mainly on Class Councils practice.(AU)